Melatonin improves the fertilization capacity and developmental ability of bovine oocytes by regulating cytoplasmic maturation events - Zhao, Xue‐Ming; Wang, Na; Hao, Hai‐Sheng; Li, Chong‐Yang; Zhao, Ya‐Han; Yan, Chang‐Liang; Wang, Hao‐Yu; Du, Wei‐Hua; Wang, Dong; Liu, Yan; Pang, Yun‐Wei; Zhu, Hua‐Bin (Journal of pineal research, 2018)
Melatonin is a well‐characterized antioxidant that has been successfully used to protect oocytes from reactive oxygen species during in vitro maturation (IVM), resulting in improved fertilization capacity and development ability. However, the mechanism via which melatonin improves oocyte fertilization capacity and development ability remains to be determined. Here, we studied the effects of melatonin on cytoplasmic maturation of bovine oocytes. In the present study, bovine oocytes were cultured in IVM medium supplemented with 0, 10–7, 10–9, and 10−11 mol/L melatonin, and the cytoplasmic maturation parameters of MII oocytes after IVM were investigated, including redistribution of organelles (mitochondria, cortical granules [CGs], and endoplasmic reticulum [ER]), intracellular glutathione (GSH) and ATP levels, expression of endogenous antioxidant genes (Cat, Sod1, and GPx), and fertilization‐related events (IP3R1 distribution and expression of CD9 and Juno). Our results showed that melatonin significantly improved the cytoplasmic maturation of bovine oocytes by improving the normal distribution of organelles, increasing intracellular GSH and ATP levels, enhancing antioxidant gene expression levels, and modulating fertilization‐related events, all of which resulted in increased fertilization capacity and developmental ability. Meanwhile, melatonin also increased the mRNA and protein expression levels of the Tet1 gene and decreased the Dnmt1 gene mRNA and protein levels in bovine oocytes, indicating that melatonin regulates the expression of the detected genes via demethylation. These findings shed insights into the potential mechanisms by which melatonin improves oocyte quality during IVM.